2015
DOI: 10.1016/j.ccell.2015.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Mutant U2AF1 Expression Alters Hematopoiesis and Pre-mRNA Splicing In Vivo

Abstract: SUMMARY Heterozygous somatic mutations in the spliceosome gene U2AF1 occur in ~11% of patients with myelodysplastic syndromes (MDS), the most common adult myeloid malignancy. It is unclear how these mutations contribute to disease. We examined in vivo hematopoietic consequences of the most common U2AF1 mutation using a doxycycline-inducible transgenic mouse model. Mice expressing mutant U2AF1(S34F) display altered hematopoiesis and changes in pre-mRNA splicing in hematopoietic progenitor cells by whole transcr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

32
286
4
19

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 263 publications
(347 citation statements)
references
References 54 publications
32
286
4
19
Order By: Relevance
“…To confirm that somatic gene mutations prime HSPCs for pyroptosis in MDSs, we performed comparative analyses of published gene expression profiles from human and murine SRSF2 (GSE65349) and U2AF1 mutants (GSE30195 and GSE66793) vs WT, TET2 knockout (GSE27816), and primary MDS (GSE19429) vs normal HSPCs and found uniform upregulation of pyroptosis effectors, consistent with transcriptional priming. [39][40][41][42][43] Importantly, in MDS BM specimens, BM plasma concentration of S100A9 positively correlated with NLRP3 MFI, percentage and MFI of plasma ASC specks, and the presence of SGMs and variant allele frequency (supplemental Figure 8). Furthermore, both the percentage and MFI of plasma ASC specks were significantly increased in MDS patients harboring SGMs (supplemental Figure 8D-E).…”
Section: Org Frommentioning
confidence: 90%
“…To confirm that somatic gene mutations prime HSPCs for pyroptosis in MDSs, we performed comparative analyses of published gene expression profiles from human and murine SRSF2 (GSE65349) and U2AF1 mutants (GSE30195 and GSE66793) vs WT, TET2 knockout (GSE27816), and primary MDS (GSE19429) vs normal HSPCs and found uniform upregulation of pyroptosis effectors, consistent with transcriptional priming. [39][40][41][42][43] Importantly, in MDS BM specimens, BM plasma concentration of S100A9 positively correlated with NLRP3 MFI, percentage and MFI of plasma ASC specks, and the presence of SGMs and variant allele frequency (supplemental Figure 8). Furthermore, both the percentage and MFI of plasma ASC specks were significantly increased in MDS patients harboring SGMs (supplemental Figure 8D-E).…”
Section: Org Frommentioning
confidence: 90%
“…17 The study population was selected on the basis of the availability of sufficient DNA and was not otherwise biased by any other selection criteria. Targeted capture assays were carried out on bone marrow or whole blood DNA for the following genes: TET2 (exons 3, 9, 10, and 11), DNMT3A (exons 4,8,13,15,16,18,19,20,22, and 23), IDH1 (exon 4), IDH2 (exon 4), ASXL1 (exon 12), EZH2 (exons 8, 17, and 18), SUZ12 (all exons), SRSF2 (exon 1), SF3B1 (exons 13, 15, and 17), ZRSR2 (all exons), U2AF1 (exons 2 and 6), PTPN11 (all exons), TP53 (exons 5, 6, 7, and 8), SH2B3 (all exons), RUNX1 (exons 3, 4, and 8), CBL (exons 8 and 9), NRAS (exons 2 and 3), JAK2 (exons 12 and 14), CSF3R (exons 14 and 17), FLT3 (exons 14 and 20), KIT (all exons), CALR (all exons), MPL (exon 10), NPM1 (exon 11), CEBPA (exon 1), IKZF1 (all exons), and SETBP1 (exon 3).…”
Section: Methodsmentioning
confidence: 99%
“…57,59 Further insights into the functional consequences of splicing factor gene mutations have been gained through in vivo modeling of the U2AF1 hotspot mutation in a transgenic mouse model, which altered hematopoiesis associated with changes in pre-mRNA splicing of genes that are recurrent mutation targets in MDS and AML including BCOR and KMT2D (MLL2). 60 A recent complementary study focusing on SRSF2 showed that the mutation impairs hematopoietic differentiation in vivo. SRSF2 mutation was found to alter the binding specificity of SRSF2 to splice recognition motifs leading to missplicing of targets such as EZH2, thereby explaining the mutual exclusivity of EZH2 and SRSF2 mutations in myeloid malignancy.…”
Section: Splicing Factor Gene Mutationsmentioning
confidence: 99%